The baby-sitters club Kristy's great ides - Martin, Ann M (New York, NY Graphix, an imprint of Scholastic, 2015)
"Kristy, Mary Anne, Claudia, and Stacey are best friends and founding member of The Baby-sitters Club. Whatever comes up--cranky toddlers, huge dogs, scary neighbors, prank calls--you can count on them to save the day. Baby-sitting isn't always easy, and neither is dealing with strict parents, new families, fashion emergencies, and mysterious secrets. But no matter what, the BSC have what they need most: friendship"--Back cover, v. 1
Comic strips
2